Os desafios para demarcação de Terra Indígena Chiquitana Portal do Encantado - Santana, Miguel Ferreira (2020)
As time passed, the Chiquitanos suffered an increasing spoliation of their traditional territory. On the Brazil-Bolivia border strip, there are no Chiquitan lands demarcated in Brazil. The present research is based on anthropological reports related to the Portal do Encantado Indigenous Land, located in the municipalities of Porto Esperidião, Vila Bela da Santíssima Trindade and Pontes e Lacerda in the State of Mato Grosso, until then the only one that was officially studied by a Technical Group officially established by FUNAI and is in the process of demarcation. I will discuss the guarantee of the rights of indigenous ethnicities and the laws of land in Brazil with its landmark in the 1988 Constitution. The landowners who took political power systematically enter into challenges to the demarcation process in the Federal Court, which means that manage to enforce the right to traditional Chiquitan territory. The reading of the Reports that are attached to the Process of demarcation of the Portal do Encantado Indigenous Land was important to understand the political-economic field of disputes verified in the legal scope. On December 30, 2010, the Portal do Encantado Indigenous Land was created as a last act of the Lula government, but the Chiquitans have not yet had sufficient political strength to demarcate and ratify the Portal do Encantado.